Climate-related economic losses in Taiwan. (2017) - Chen, Ling-Ling; Tseng, Chao-Heng; Shih, Yi-Hsuan
The objective of this study is to quantify the relationship between CO2 emissions and economic losses under the Intergovernmental Panel on Climate Change Special Report on Emissions Scenarios (SRES) A2, A1B and B1. Previous trend is used to formulate predictions with regard to future climate-related hazards and quantify the expected economic consequences for Taiwan. We establish an equation with which to forecast economic losses related to agricultural damage, death toll, and medical expenditures. The results are as follows: 1) according to SRES A2, A1B and B1 projections, cumulative total economic losses of unit CO2 emission between 2013 and 2100 are US$ 75-261/tCO2, US$ 76-215/tCO2, and US$ 75-169/tCO2, respectively; 2) total economic losses related to natural disaster exhibits a strong correlation with GDP between 1991 and 2012, compares to the period from 1971 to 1990 (this is not including the medical expenditure losses in the total economic losses); 3) according to SRES's A1B scenario, predicted total economic losses related to natural disasters are expected to be strongly correlated with GDP between 2013 and 2100.